The Mantis : b a novel - Isaka, Kōtarō, 1971- (Overlook Press, 2023)
"Kabuto is a highly skilled assassin eager to escape his dangerous profession and the hold his handler, the sinister Doctor, has over him. The Doctor, a real physician who hands over Kabuto's targets as "prescriptions" in his regular appointments with him, doesn't want to lose Kabuto as a profitable asset, but he agrees to let him pay his way out of his employment with a few last jobs. But the most lucrative jobs involve taking out other professional assassins, and Kabuto's final assignment puts him and his family--who have no idea about his double life--in danger.The third book in a loose trilogy set in Kotaro Isaka's imagined Tokyo criminal underworld, The Mantis features all the hallmarks of his work that readers have come to crave--assassins with quirky codenames and modi operandi, page-turning action sequences, madcap energy, and razor-sharp humor--making the novel a frenetic, unputdownable read that hurtles readers toward a thrilling climax." --Amazon.